Severe Acute Respiratory Failure Associated with Viral Respiratory Infections: A Multidisciplinary Approach to Diagnosis, Pharmacotherapy, Respiratory Support, and Critical Care Management - Hassan Ali Kaseb; Khalid Jadaan Alotaibi; Hassan Hasser Hassan Hassany; Riyadh Hassan Kaabi; Alhammadi; Omar Muteb; Shoroug Hamoud AlSawadi; Shaima Mohammed Madkhali; Rawan Bader Almutairi; Abdulaziz Mohammad Al Zahrani; Reem Morfoua Alshammari; Moneerah Shaman Fahid Aljuhani; et al. (Saudi Journal of Medicine and Public Health, 2026)
Background: Severe acute respiratory failure caused by respiratory viruses is an important cause of intensive care unit admission and is associated with substantial morbidity and mortality. Advances in molecular diagnostics have increased the detection of respiratory viruses in lower respiratory tract infections, while also highlighting challenges in distinguishing true viral disease from asymptomatic carriage and bacterial-viral co-infection. Respiratory viruses can cause direct epithelial injury, dysregulated inflammation, alveolar damage, and systemic complications. Aim: This narrative review aimed to summarize current evidence on the epidemiology, molecular diagnosis, pathophysiology, clinical consequences, outcomes, treatment, and prevention of severe respiratory viral infections causing acute respiratory failure in immunocompetent adults. Methods: A narrative review of published clinical and experimental evidence was conducted. The review focused on respiratory viruses causing community-acquired severe respiratory infections in immunocompetent adults, excluding SARS-CoV-2 and herpesviruses. Evidence concerning molecular diagnostic techniques, respiratory support, antiviral therapy, immunomodulation, outcomes, and vaccination was synthesized. Results: Multiplex PCR has improved detection of respiratory viruses and bacterial-viral co-infections, with reported viral detection rates varying according to the population and sampling method. Influenza, respiratory syncytial virus, and human metapneumovirus are important causes of severe disease. Viral epithelial injury, cell death, immune dysregulation, and diffuse alveolar damage contribute to respiratory failure. Bacterial co-infections and cardiovascular complications further increase mortality. Management remains primarily supportive, although oseltamivir remains central for severe influenza. Evidence for corticosteroids in viral pneumonia is limited and inconsistent. Vaccination provides an important strategy for reducing severe disease, particularly among older adults. Conclusion: Respiratory viruses represent important causes of severe acute respiratory failure. Early molecular diagnosis, appropriate respiratory support, pathogen-directed treatment, prevention of co-infections, and vaccination are central to improving outcomes.